Filippo Maria De Sanctis e l’educazione cinematografica. Marxismo, educazione permanente, contrastività - Felini, Damiano (Studi sulla Formazione/Open Journal of Education, 2017)
The works of Filippo Maria De Sanctis (1926-1989) on film education represent an original contribution in the landscape of media pedagogy, Marxist and other-wise, of the 1960s and 1970s. The article first outlines the main leans in screen education of the time, before it reconstructs De Sanctis’ contribution in this area, connecting it to the other core topic of his work (for which he is best remembered today): lifelong learning. In doing so, the article focuses on the method of post-film discussion, used in the context of both film clubs and schools. Criti-cally analyzing De Sanctis’ media pedagogy, the article reveals, beyond the orig-inality of the author, interesting insights regarding the historical evolution of the field, such as the problematic theorization of the inoculation/protectionist model, and the end of the orientation aimed at the aesthetic development of the human subject.